Application of the Discovery Learning Modelto Increase Communication Skills Mathematics of Class X IPA-6 Students - Nasution, Miftahul Rizka (JMEA : Journal of Mathematics Education and Application, 2024)
This research aims to improve students' mathematical communication skills through the application of the Discovery Learning learning model in Trigonometry material in class X SMA Negeri 11 Medan . This type of research is classroom action research. The subjects of this research were class X IPA-6 students SMA Negeri 11 Medan, totaling 32 people. The object of this research is students' mathematical communication skills by applying the discovery learning model to trigonometry material.Based on data analysis, students' mathematical communication abilities in cycle I were obtained 18 students (56.25%) out of 32 students have achieved learning completion (). After action II, through administering the Mathematics Communication Skills Test II, 27 students (84.375 %) of the 32 students had achieved learning completion (). There was an increase in the percentage of classical completion by 28.125%. Based on the classical completeness criteria, this completeness percentage is fulfilled. The average score of the mathematics communication skills test results in cycle I was 69.88 and in cycle II it increased to 83.16. The increase in average value was 13.28 with a Gain Score of 0.44 which was in the medium category. Based on the descriptions above, it can be concluded that students' mathematical communication improves by applying the discovery learning model to Trigonometry material in class X IPA-6 at SMA Negeri 11 Medan.